Omega loop jejunostomy with definitive detransitation: Technical modification of the Bérard and Alamartine procedure - Pignata, Daniel; Estefan, Alberto; Pomi, Jorge; Beguiristain, Alberto (Cirugía del Uruguay, 1979)
The authors describe a technical modification o·f jejunostomy in omega loop, consisting in detransitation in its afferent branch by means of intestinal sectioning. In this manneer a functional jejunostomy is formed, similar to classic "Y" jejunostomy, with obvio'us advantages: it is simply and quickly performed and requires no mesenteric section. This procedures was employed in 4 patients with good results.